Excellent Service Quality at V-Coffee Padang - Febriyanti, Lucy; Siregar, Juliana (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
The findings of the study do not support the idea that the authors examined, contrary to the author's first observations of the outstanding service provided at V-Coffee Padang. This study intends to define Excellent Service and Consumer Satisfaction at V-Coffee Padang and determine whether there is a relationship between the two. The research methodology is causal associative quantitative research. 5,200 customers have stopped by V-Coffee Padang in the past three months, making up the population. By giving out surveys about great service and customer happiness to up to 98 people, the sampling technique used incidental sampling. Before performing the hypothesis test, analytical requirements tests such as the coefficient of determination test, simple linear regression analysis, linearity test and homogeneity test are conducted using SPSS version 28.00. As of this writing, the consumer satisfaction variable (Y) and the exceptional service variable (X) are both included in the fairly good group with percentages of 46.9% and 63.3%, respectively. At V-Coffee Padang, the outstanding service variable has a 0.688 correlation to customer satisfaction, indicating a significant and favorable association between the two factors. The regression coefficient is 0.637, and the determination coefficient is (0.473) 47.3% and 52.7% are influenced by other factors.